Analysis of the Influence of Lifestyle, Market Attractiveness, and HR Capabilities on Product Innovation and Customer Value Implications - Utama, Adi (Almana : Jurnal Manajemen dan Bisnis, 2023)
One of the successes of a company operating in the service sector will depend greatly on the marketing strategy implemented by the company and the quality of employee service to consumers, as well as a comfortable and strategic location. As is known, customer value will be largely determined by product innovation. Product innovation will be determined by lifestyle, market attractiveness, and human resource capabilities. This research aims to determine and examine the influence of lifestyle, market attractiveness, and human resource capabilities on product innovation and the customer value implications of coffee shops in Greater Bandung. This research uses quantitative methods with descriptive analysis and verification analysis approaches. In this research, the samples were coffee shop customers, totaling 399 customers. The analytical tool in this research uses SEM (Structural Equation Model) analysis. The research results concluded that there is a significant influence of lifestyle, market attractiveness, and human resource capabilities on product innovation, and there is a significant influence of product innovation on customer value.